Anticorrosive coating for ship bottom and preparation method thereof

By using boron nitride to coat capsaicin filler and boron nitride modified fluorosilicone copolymer in anticorrosion coatings, the shortcomings of existing coatings in wear resistance, corrosion resistance and inhibition of marine biological adhesion are solved, and the goal of high-performance anticorrosion coatings is achieved.

CN119060602BActive Publication Date: 2025-03-14JIANGSU MARINE VICTORY COATING

Patent Information

Application Number
CN202411561726.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-03-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Existing anticorrosion coatings have shortcomings in wear resistance, corrosion resistance and inhibition of marine biological adhesion, and it is difficult to meet the needs of high-performance anticorrosion coatings.

Method used

Boron nitride coated with capsaicin filler and boron nitride modified fluorosilicone copolymer were prepared by sonication and spray drying to form a low-surface free energy coating to enhance the wear resistance, stain resistance and corrosion resistance of the coating.

Benefits of technology

It significantly improves the wear resistance, stain resistance and corrosion resistance of the coating, extends the service life of the coating, reduces marine biological adhesion, and provides a comprehensive protection effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119060602B_ABST
    Figure CN119060602B_ABST
Patent Text Reader

Abstract

The invention relates to the field of coating materials, and provides an anticorrosive coating for the bottom of a ship and a preparation method thereof, which is made of the following components: a boron nitride coated capsaicin filler, a boron nitride modified fluorine silicon copolymer, a fluorine phosphorus monomer modified waterborne acrylic emulsion, an epoxy resin, a film former, a defoamer, a dispersant, an initiator, a preservative and deionized water; the preparation method of the coating: the filler is first dispersed in a high speed in a stirring kettle with deionized water, a boron nitride coated capsaicin, a boron nitride modified fluorine silicon copolymer and a dispersant according to a proportion to form a dispersed solution, and then the solution is injected into a paint mixing tank, and the fluorine phosphorus monomer modified waterborne acrylic emulsion, an epoxy resin, a preservative, a film former and a defoamer are added, heated and stirred, and then cooled to room temperature. The anticorrosive coating of the invention has excellent properties such as high wear resistance, high corrosion resistance and inhibition of marine biological attachment, so as to meet the demand for high-performance anticorrosive coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coating materials, and in particular to an anti-corrosion coating for a ship bottom and a preparation method thereof. Background Art

[0002] The use of anti-corrosion coatings on the bottom of ships is an important measure for navigation and ship protection. During long underwater voyages, the bottom of ships is susceptible to corrosion, biological attachment and oxidation in the marine environment, which can cause damage to the metal structure. In order to protect the bottom of ships and extend their service life, the application of anti-corrosion coatings is particularly critical. The demand for anti-corrosion coatings includes multiple aspects. First, anti-corrosion coatings need to have excellent corrosion resistance and can effectively resist the erosion of salt water, oxidation and chemicals in the marine environment, thereby protecting the integrity of the metal structure at the bottom of the ship. Secondly, anti-corrosion coatings should have the ability to inhibit the attachment of marine organisms, reduce the growth of algae, shells and other organisms, reduce the friction resistance of the hull, and improve navigation efficiency. In addition, wear resistance is also an important demand, because the bottom of the ship is susceptible to water flow and friction, and good wear resistance can extend the service life of the coating. Finally, considering the requirements of environmental protection, anti-corrosion coatings should minimize the impact on the marine ecosystem and avoid the use of harmful substances. The development of anti-corrosion coatings for the bottom of ships is of great significance. By using high-performance anti-corrosion coatings, the service life of ships can be extended, the maintenance frequency and cost can be reduced, and the reliability and economic benefits of ships can be improved. In addition, the innovation and development of anti-corrosion coatings can also reduce the environmental impact of ship operations and protect the health of marine ecosystems. With the continuous advancement of technology, future development directions will include more environmentally friendly, efficient and intelligent anti-corrosion coatings to meet the needs of the continuous evolution and sustainable development of the shipping industry.

[0003] At present, although anti-corrosion coatings have made a lot of progress, there are still some shortcomings. (1) The wear resistance of the coating still needs to be further improved to meet the water flow friction requirements during the navigation of ships. For example, the Chinese patent with publication number CN101260273B discloses a flexible epoxy anti-corrosion coating. This patent mainly focuses on the improvement of flexibility and corrosion resistance, but there is no mechanism to improve the wear resistance in terms of wear resistance, so the wear resistance still has certain limitations. (2) The realization and maintenance of anti-corrosion performance is still one of the technical difficulties. Ships sail in high-salinity seawater for a long time and need to maintain long-term corrosion resistance. (3) Insufficient inhibition of marine biological attachment is also a key factor restricting the application scope of coatings. When the coating contacts certain organisms, it usually destroys the coating. Therefore, anti-corrosion coatings currently still face many challenges in terms of wear resistance, corrosion resistance and inhibition of marine biological attachment. In order to fill this technical gap, it is necessary to develop a new type of anti-corrosion coating that has high wear resistance, high corrosion resistance and inhibition of marine biological attachment to meet the needs of high-performance anti-corrosion coatings. Summary of the invention

[0004] (1) Technical problems solved

[0005] The purpose of the present invention is to provide an anti-corrosion coating for the bottom of a ship and a preparation method thereof, so as to solve the problems that the current anti-corrosion coating is insufficient in terms of wear resistance, corrosion resistance and inhibition of marine organism attachment.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] An anticorrosive coating for the bottom of a ship is prepared from the following components in parts by weight: 8-16 parts of boron nitride coated capsaicin filler, 10-18 parts of boron nitride modified fluorosilicon copolymer, 30-45 parts of fluorophosphorus monomer modified waterborne acrylic emulsion, 6-10 parts of epoxy resin, 10-18 parts of film former, 2-4 parts of defoamer, 2-5 parts of dispersant, 3-6 parts of preservative and 5-10 parts of deionized water.

[0009] The preparation method of the boron nitride coated capsaicin filler is as follows: after 50 to 80 parts of porous boron nitride hollow microspheres, 10 to 20 parts of capsaicin and 80 parts of ethanol are mixed evenly by weight, the mixture is placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 80 to 100 W, the time is 15 to 30 minutes, filtering is performed after ultrasonic treatment, and the filtered product is washed once with a mixed solution of ethanol and water in a mass ratio of 1:1 to remove excess capsaicin on the surface of the porous boron nitride hollow microspheres, and then dried to obtain the boron nitride coated capsaicin filler.

[0010] The average particle size of the boron nitride coated capsaicin filler is 500-2000 nm.

[0011] The preparation method of the boron nitride modified fluorosilicon copolymer is as follows: in a nitrogen atmosphere, 22 to 30 parts by weight of dodecafluoroheptyl methacrylate, 11 to 15 parts of methacryloyloxypropyl trimethoxysilane, 44 to 60 parts of glycidyl methacrylate, 44 to 60 parts of butyl acrylate and 2 to 4 parts of azobisisobutyronitrile are mixed evenly to obtain a fluorosilicon prepolymer solution for use. 15 to 30 parts of methyl methacrylate and 3 to 6 parts of boron nitride are mixed evenly and heated to 65 to 85° C., and then the fluorosilicon prepolymer solution is dripped therein, and after the dripping is completed, the reaction is stirred for 2 to 4 hours, and after the reaction is completed, the temperature is cooled to room temperature to obtain a boron nitride modified fluorosilicon copolymer.

[0012] The preparation method of the fluorophosphorus monomer modified waterborne acrylic emulsion is as follows: by weight, 10-15 parts of methyl methacrylate, 20-28 parts of butyl acrylate, 3-6 parts of acrylic acid, 2-4 parts of isooctyl acrylate, 3-6 parts of glycidyl methacrylate, 2-4 parts of sodium dodecyl sulfate and 25-45 parts of deionized water are mixed and stirred for 30-60 minutes for pre-emulsification treatment, then 8-15 parts of fluorine-containing monomer and 8-15 parts of phosphorus-containing monomer are added, heated to 60-80° C. and stirred for 30-60 minutes, then 2-5 parts of potassium persulfate are added and stirred for 1 hour, and finally the temperature is reduced and cooled to obtain the fluorophosphorus monomer modified waterborne acrylic emulsion.

[0013] Furthermore, the preparation method of capsaicin is as follows: by weight, 50-70 parts of dried devil peppers are deseeded and stalked, added to 100 parts of anhydrous ethanol, crushed with a tissue crusher, and then placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 90-110W, the time is 30-60min, and then the ultrasonic solution is filtered to obtain a first filtrate and a first filter residue, the first filter residue is subjected to a second ultrasonic filtration treatment using the same process and parameters to obtain a second filtrate and a second filter residue, the first filtrate and the second filtrate are mixed and evaporated at 45-55°C for 2-4h to obtain a capsaicin concentrate, and then dried completely at 50-80°C to obtain capsaicin.

[0014] Furthermore, the Scoville heat of the capsaicin is 40,000-80,000.

[0015] Furthermore, the preparation method of the porous boron nitride hollow microspheres is as follows: 15 to 30 parts of boric acid and 30 to 60 parts of urea are dissolved in 100 parts of deionized water, stirred at 40 to 50°C for 12 to 24 hours, and then a spray drying method is used to obtain boron nitride precursor microspheres, and then the boron nitride precursor microspheres are placed in a high-temperature tubular furnace and calcined in a nitrogen atmosphere. The calcination parameters are: heating from room temperature to 450 to 500°C at 5°C / min and keeping warm for 2 hours, and then continuing to heat to 950 to 1200°C at 5°C / min and keeping warm for 2 hours, and then naturally cooling to room temperature to obtain a white product. The white product was completely submerged with 1 mol / L hydrochloric acid solution, stirred at room temperature for 6 to 10 hours, and then filtered to obtain a filtered product. The filtered product was then washed three times with a mixed washing solution of deionized water and anhydrous ethanol in a mass ratio of 1:1. Each washing required that the filtered product be completely submerged with the washing solution. Finally, the washed product was dried to obtain porous boron nitride hollow microspheres.

[0016] Furthermore, the mass ratio of the boric acid to urea is 1:2.

[0017] Furthermore, the parameters of the spray drying method are: inlet flow rate is 5-10 ml / min, nozzle pressure is 1-3 bar, and inlet temperature is 100-120°C.

[0018] This design of capsaicin coated with boron nitride has the following multiple purposes: 1. Boron nitride coating provides a wear resistance enhancement mechanism for the anti-corrosion coating on the bottom of the ship. Boron nitride has excellent hardness and wear resistance. It forms a protective layer on the surface of the bottom coating, which can reduce friction and wear and extend the service life of the coating. 2. As a component of anti-fouling coating, capsaicin, a biological extract of devil pepper, has an ultra-high Scoville spiciness and has the characteristic of "only driving away but not killing". Capsaicin has a certain repelling effect on marine organisms and can prevent marine organisms from attaching to the surface of ships, thereby reducing the problems caused by biological corrosion and attachment. 3. The porous microsphere structure of boron nitride can slowly release capsaicin and increase the service life of the coating. The microporous structure is conducive to the controlled release of capsaicin, so that it forms a protective layer on the surface of the coating and slows down its consumption rate. 4. The design of capsaicin coated with boron nitride can prevent capsaicin from toxicating the coating. The boron nitride coating can effectively isolate the contact between capsaicin and the coating, reduce its toxic effect, and maintain the performance stability of the coating. 5. This design of capsaicin coated with boron nitride also has the characteristics of anti-corrosion. In addition, the boron nitride coating forms a protective layer on the surface of the ship bottom coating, effectively isolating the metal surface from contact with external corrosive media. Boron nitride has the characteristics of chemical inertness and non-conductivity, which reduces the reaction with corrosive media such as acids, alkalis, and solvents, thereby preventing corrosion of the metal surface. In summary, through the multiple mechanisms of boron nitride coating capsaicin, the design achieves the purpose of increasing the wear resistance, anti-fouling, non-toxicity of the coating and improving the life of the coating, providing a comprehensive protection effect for the ship bottom anti-corrosion coating.

[0019] Furthermore, the mass ratio of dodecafluoroheptyl methacrylate, methacryloyloxypropyltrimethoxysilane, glycidyl methacrylate and butyl acrylate is 2:1:4:4.

[0020] The present invention adopts boron nitride to modify the fluorosilicon copolymer with the following multiple purposes: 1. This design focuses on the construction of low surface free energy coatings. In the fluorosilicon copolymer system, through the introduction of carefully designed fluorine-containing side chains and silicon-containing side chains, the synergistic effect of the two gives the coating a significant reduction in surface free energy. Specifically, the fluorine-containing side chains, with their lower surface free energy, are easy to aggregate at the solid-gas interface to form an effective barrier layer, effectively preventing moisture penetration. At the same time, the silicon-containing side chains not only stabilize the fluorine groups and inhibit the regeneration of the surface groups of the coating, but also further enhance the waterproof performance of the coating by shielding the main chain of the copolymer. This design strategy significantly reduces the surface free energy of the coating, thereby giving the coating excellent hydrophobic properties. 2. Enhanced antifouling performance: Another important goal of the present invention is to enhance the antifouling performance of the coating. By reducing the surface free energy of the coating, this design successfully reduces the adhesion ability of biological fouling, thereby significantly reducing the accumulation of fouling. 3. At the same time, the introduction of boron nitride further enhances the antifouling effect of the coating, and its unique nanostructure can effectively inhibit the growth of microorganisms through mechanisms such as nanoknife. 4. In terms of corrosion resistance, the present invention also performs well. Boron nitride is evenly dispersed in the coating in a layered structure, which significantly improves the shielding performance of the coating. 5. Self-repairing corrosion resistance. During the penetration of the electrolyte, the hydrolyzable alkoxy groups in the coating will undergo a hydrolysis reaction under the action of water to generate silanols, which are then further condensed to form a dense network-like Si-O-Si structure. This process not only increases the degree of cross-linking of the coating, but also reduces the porosity of the coating, thereby significantly improving the corrosion resistance of the coating. In summary, the present invention achieves the construction of a low surface free energy coating by modifying a fluorosilicon copolymer with boron nitride, significantly improves the hydrophobic, anti-fouling and corrosion resistance of the coating, and gives it self-repairing corrosion resistance, providing important technical support for the application of coating materials in multiple fields.

[0021] Furthermore, the fluorine-containing monomer is 2,2,2-trifluoroethyl acrylate or 2,2,2-trifluoroethyl methacrylate or octafluoropentyl methacrylate.

[0022] Furthermore, the phosphorus-containing monomer is polyethylene glycol methacrylate phosphate.

[0023] The present invention aims to achieve multiple improvement effects by introducing fluorinated phosphorus monomers to modify the water-based acrylic emulsion. This not only significantly improves the water resistance, corrosion resistance and adhesion to the substrate of the coating, but also shows great application potential in the field of anti-corrosion coatings. The following is a detailed explanation of these improvement effects: 1. Significant improvement in water resistance: The introduction of fluorinated monomers greatly enhances the hydrophobicity of the coating, making it difficult for water to form a wetting layer on the surface of the coating, thereby significantly improving the water resistance of the coating. Further, during the curing process, the fluorinated side chains migrate to the surface of the coating to form a dense hydrophobic fluorinated layer. This fluorinated layer not only effectively reduces the direct contact between water and the coating, but also successfully blocks the penetration of water into the coating, further consolidating the water resistance of the coating. 2. Significant enhancement of corrosion resistance: The introduction of phosphate functional monomers significantly improves the adhesion between the resin and the substrate. This is because the phosphate group can form a stable chemical bond with the metal substrate, thereby enhancing the bonding force between the coating and the substrate, and effectively preventing the coating from peeling and falling off in the corrosive medium. In addition, due to the presence of the fluorinated layer, the coating surface becomes smoother and less susceptible to corrosion by corrosive media, further improving the corrosion resistance of the coating. 3. Synergistic effect of the fluorinated layer and the phosphate group: The fluorinated layer blocks the penetration of moisture and corrosive media through its excellent hydrophobicity, while the phosphate group enhances the adhesion between the coating and the substrate, thereby jointly improving the anti-corrosion performance of the coating. This synergistic effect enables the coating to perform well in terms of anti-corrosion performance, with excellent water resistance and corrosion resistance. In summary, the present invention successfully prepared a new type of water-based acrylic resin with excellent performance by modifying the water-based acrylic emulsion with fluorophosphorus monomers. This resin has broad application prospects in the field of water-based anti-rust coatings and is expected to provide a new solution for the anti-corrosion protection of ships.

[0024] Furthermore, the preparation method of the epoxy resin is as follows: by weight, 25-35 parts of furfurylamine, 10-18 parts of bisphenol A diglycidyl ether and 10-15 parts of dimethylformamide are uniformly mixed and reacted at 55-65° C. for 3-5 hours to obtain the epoxy resin.

[0025] Furthermore, the preservative is 4,5-dichloro-N-octyl-4-isothiazoline-3-one.

[0026] Furthermore, the film-forming agent is ethylene glycol butyl ether or ethylene glycol ether.

[0027] Furthermore, the defoamer is an organic silicon defoamer or a polyether-modified silicone oil defoamer.

[0028] Furthermore, the dispersant is polyacrylate sodium salt or polyacrylate ammonium salt.

[0029] In the anti-corrosion coating on the bottom of the ship, the anti-corrosion agent plays a key role. It can effectively inhibit the growth of microorganisms and corrosion reactions, and extend the protective life of the coating; the film-forming agent helps the coating form a strong and uniform film layer on the bottom of the ship, enhancing the adhesion and durability of the coating; the defoaming agent is used to eliminate bubbles generated by the coating during the coating process to ensure the smoothness and quality of the coating; the dispersant ensures that the filler is evenly distributed in the coating, improving the stability and performance of the coating. These agents work together to provide strong anti-corrosion protection for the bottom of the ship.

[0030] The present invention also provides a method for preparing an anticorrosive coating for a ship bottom, comprising the following steps:

[0031] S1: Dispersion of filler: Deionized water, boron nitride coated capsaicin filler, boron nitride modified fluorosilicone copolymer and dispersant are added into a stirring tank according to the proportion, and dispersed at a high speed of 800 to 1200 rpm for 30 to 50 minutes to obtain a filler dispersion solution.

[0032] S2: Prepare coating: inject the filler dispersion solution obtained in S1 into the paint mixing tank, continue to add fluorophosphorus monomer modified water-based acrylic emulsion, epoxy resin, preservative, film-forming agent, defoaming agent into the paint mixing tank, stir at 100-200 rpm for 30-50 minutes at 75-85°C, and cool to room temperature after stirring.

[0033] (3) Beneficial technical effects

[0034] The design of capsaicin coated with boron nitride shows multiple advantages in the anti-corrosion coating for ship bottom. First, the introduction of boron nitride not only greatly enhances the wear resistance of the coating and significantly extends its service life, but also effectively drives away marine organisms with the help of the natural antifouling properties of capsaicin, significantly reducing the risk of biocorrosion. Secondly, the porous structure of boron nitride cleverly controls the release of capsaicin, forming a long-lasting and stable protective layer, effectively isolating the possible toxicity of capsaicin and ensuring the stable performance of the coating. In addition, the design also has excellent anti-corrosion function. The chemical inertness and non-conductivity of boron nitride enable the coating to effectively resist the erosion of external corrosive media, providing comprehensive anti-corrosion protection for the bottom of the ship. At the same time, the low surface free energy coating constructed by boron nitride modified fluorosilicon copolymer achieves a perfect combination of hydrophobicity, antifouling and anti-corrosion. The synergistic effect of fluorosilicon side chains significantly reduces the surface energy of the coating, while the addition of boron nitride further enhances the antifouling ability of the coating and improves its shielding performance. What is even more exciting is that the coating also has self-healing ability. Through hydrolysis reaction, a dense Si-O-Si structure is formed, which not only improves the cross-linking degree of the coating, but also reduces the porosity, thereby significantly improving the anti-corrosion performance. This innovative design provides important technical support for the application of coating materials in multiple fields. In another breakthrough invention, we modified the water-based acrylic emulsion with fluorophosphorus monomers, significantly improving the water resistance, corrosion resistance and substrate adhesion of the coating. The hydrophobic fluorinated layer formed by the fluoromonomer effectively reduces the penetration of water, while the phosphate ester enhances the bonding between the coating and the substrate. The synergistic effect of the two not only provides a high-performance resin in the field of water-based anti-rust coatings, but also provides a new solution for the anti-corrosion protection of ships. Finally, the key reagents such as preservatives, film formers, defoamers and dispersants in the anti-corrosion coatings for the bottom of the ship work together to provide strong and comprehensive anti-corrosion protection for the bottom of the ship, ensuring the safe and stable operation of the ship in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a scanning electron microscope morphology image of the porous boron nitride hollow microspheres prepared in Example 1 of the present invention.

[0036] Figure 2 This is a scanning electron microscope morphology image of the boron nitride coated capsaicin filler prepared in Example 1 of the present invention.

[0037] Figure 3 This is a phase analysis diagram of the porous boron nitride hollow microspheres prepared in Example 1 of the present invention.

[0038] Figure 4 This is a phase analysis diagram of the boron nitride coated capsaicin filler prepared in Example 1 of the present invention.

[0039] Figure 5 This is the Fourier transform infrared spectrum of the boron nitride modified fluorosilicone copolymer of Example 1 of the present invention. DETAILED DESCRIPTION

[0040] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0041] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0042] Example 1

[0043] An anticorrosive coating for the bottom of a ship is prepared from the following components in parts by weight: 8 parts of boron nitride coated capsaicin filler, 10 parts of boron nitride modified fluorosilicon copolymer, 30 parts of fluorophosphorus monomer modified waterborne acrylic emulsion, 6 parts of epoxy resin, 10 parts of ethylene glycol butyl ether film former, 2 parts of silicone defoamer, 2 parts of polyacrylic acid sodium salt dispersant, 3 parts of 4,5-dichloro-N-octyl-4-isothiazoline-3-one and 5 parts of deionized water.

[0044] The preparation method of the boron nitride coated capsaicin filler is as follows: after mixing 50 parts of porous boron nitride hollow microspheres, 10 parts of capsaicin and 80 parts of ethanol in parts by weight, the mixture is placed in an ultrasonic cleaner for ultrasonic treatment. The ultrasonic cleaner setting parameters are: 80W, the time is 1 min, and the mixture is filtered after ultrasonic treatment. The filtered product is washed once with a mixed solution of ethanol and water in a mass ratio of 1:1 to remove excess capsaicin on the surface of the porous boron nitride hollow microspheres, and then dried to obtain the boron nitride coated capsaicin filler.

[0045] The average particle size of the boron nitride coated capsaicin filler is 500 nm.

[0046] The preparation method of the boron nitride modified fluorosilicon copolymer is as follows: in a nitrogen atmosphere, 22 parts of dodecafluoroheptyl methacrylate, 11 parts of methacryloyloxypropyl trimethoxysilane, 44 parts of glycidyl methacrylate, 44 parts of butyl acrylate and 2 parts of azobisisobutyronitrile are mixed evenly to obtain a fluorosilicon prepolymer solution for use. 15 parts of methyl methacrylate and 3 parts of boron nitride are mixed evenly and heated to 65°C, and then the fluorosilicon prepolymer solution is dripped therein, and the reaction is stirred for 2 hours after the dripping is completed. After the reaction is completed, the temperature is cooled to room temperature to obtain a boron nitride modified fluorosilicon copolymer.

[0047] The preparation method of the fluorophosphorus monomer modified water-based acrylic emulsion is as follows: in parts by weight, 10 parts of methyl methacrylate, 20 parts of butyl acrylate, 3 parts of acrylic acid, 2 parts of isooctyl acrylate, 3 parts of glycidyl methacrylate, 2 parts of sodium dodecyl sulfate and 25 parts of deionized water are mixed and stirred for 30 minutes for pre-emulsification treatment, and then 8 parts of 2,2,2-trifluoroethyl acrylate and 8 parts of polyethylene glycol methacrylate phosphate are added, heated to 60°C and stirred for 30 minutes, and then 2 parts of potassium persulfate are added and stirred for 1 hour, and finally the temperature is reduced and cooled to obtain the fluorophosphorus monomer modified water-based acrylic emulsion.

[0048] The preparation method of the capsaicin is as follows: by weight, 50 parts of dried devil peppers are deseeded and destalked, added to 100 parts of anhydrous ethanol, crushed with a tissue crusher, and then placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 90W, the time is 30 minutes, and then the ultrasonic solution is filtered to obtain a first filtrate and a first filter residue, the first filter residue is subjected to a second ultrasonic filtration treatment using the same process and parameters to obtain a second filtrate and a second filter residue, the first filtrate and the second filtrate are mixed and evaporated at 45°C for 2h to obtain a capsaicin concentrate, and then the concentrate is completely dried at 50°C to obtain capsaicin.

[0049] The Scoville heat scale of the above-mentioned capsaicin is 40,000.

[0050] The preparation method of the porous boron nitride hollow microspheres is as follows: 15 parts of boric acid and 30 parts of urea are dissolved in 100 parts of deionized water, stirred at 40°C for 12 hours, and then the boron nitride precursor microspheres are obtained by spray drying, and the parameters of the spray drying method are: the inlet flow rate is 5ml / min, the nozzle pressure is 1bar, and the inlet temperature is 100°C. Then the boron nitride precursor microspheres are placed in a high-temperature tube furnace and calcined in a nitrogen atmosphere, and the calcination parameters are: heating from room temperature to 450°C at 5°C / min and keeping it for 2 hours, and then continuing to heat up to 950°C at 5°C / min and keeping it for 2 hours, and then naturally cooling to room temperature to obtain a white product. The white product was completely submerged with a 1 mol / L hydrochloric acid solution, stirred at room temperature for 6 h, and then filtered to obtain a filtered product. The filtered product was then washed three times with a mixed washing solution of deionized water and anhydrous ethanol in a mass ratio of 1:1. Each washing required that the filtered product be completely submerged with the washing solution. Finally, the washed product was dried to obtain porous boron nitride hollow microspheres.

[0051] The preparation method of the above epoxy resin is as follows: by weight, 255 parts of furfurylamine, 10 parts of bisphenol A diglycidyl ether and 10 parts of dimethylformamide are uniformly mixed and reacted at 55° C. for 3 hours to obtain the epoxy resin.

[0052] The present invention also provides a method for preparing an anticorrosive coating for a ship bottom, comprising the following steps:

[0053] S1: Dispersion of filler: Deionized water, boron nitride coated capsaicin filler, boron nitride modified fluorosilicone copolymer and dispersant were added into a stirring tank according to the proportion, and the filler dispersion solution was obtained by high-speed dispersion at 800 rpm for 30 minutes.

[0054] S2: Prepare coating: inject the filler dispersion solution obtained in S1 into the paint mixing tank, and continue to add fluorophosphorus monomer modified water-based acrylic emulsion, epoxy resin, preservative, film-forming agent, and defoaming agent into the paint mixing tank, stir at 100 rpm for 30 minutes at 75°C, and cool to room temperature after stirring.

[0055] Example 2

[0056] The invention discloses an anticorrosive coating for the bottom of a ship, which is prepared from the following components in parts by weight: 10 parts of a boron nitride-coated capsaicin filler, 12 parts of a boron nitride-modified fluorosilicon copolymer, 35 parts of a fluorophosphorus monomer-modified water-based acrylic emulsion, 7 parts of an epoxy resin, 12 parts of an ethylene glycol ether film-forming agent, 3 parts of a polyether-modified silicone oil defoamer, 3 parts of an ammonium polyacrylate, 4 parts of 4,5-dichloro-N-octyl-4-isothiazoline-3-one and 6 parts of deionized water.

[0057] The preparation method of the boron nitride coated capsaicin filler is as follows: after mixing 50 parts of porous boron nitride hollow microspheres, 12 parts of capsaicin and 80 parts of ethanol by weight, the mixture is placed in an ultrasonic cleaner for ultrasonic treatment. The setting parameters of the ultrasonic cleaner are: 85W, the time is 16 minutes, and the mixture is filtered after ultrasonic treatment. The filtered product is washed once with a mixed solution of ethanol and water in a mass ratio of 1:1 to remove excess capsaicin on the surface of the porous boron nitride hollow microspheres, and then dried to obtain the boron nitride coated capsaicin filler.

[0058] The average particle size of the boron nitride coated capsaicin filler is 700 nm.

[0059] The preparation method of the boron nitride modified fluorosilicon copolymer is as follows: in a nitrogen atmosphere, 24 parts of dodecafluoroheptyl methacrylate, 12 parts of methacryloyloxypropyl trimethoxysilane, 48 parts of glycidyl methacrylate, 48 parts of butyl acrylate and 3 parts of azobisisobutyronitrile are mixed evenly to obtain a fluorosilicon prepolymer solution for use. 18 parts of methyl methacrylate and 4 parts of boron nitride are mixed evenly and heated to 70°C, and then the fluorosilicon prepolymer solution is dripped therein, and the reaction is stirred for 3 hours after the dripping is completed. After the reaction is completed, the temperature is cooled to room temperature to obtain a boron nitride modified fluorosilicon copolymer.

[0060] The preparation method of the fluorophosphorus monomer modified water-based acrylic emulsion is as follows: in parts by weight, 11 parts of methyl methacrylate, 22 parts of butyl acrylate, 4 parts of acrylic acid, 3 parts of isooctyl acrylate, 4 parts of glycidyl methacrylate, 3 parts of sodium lauryl sulfate and 30 parts of deionized water are mixed and stirred for 35 minutes for pre-emulsification treatment, and then 10 parts of 2,2,2-trifluoroethyl methacrylate and 10 parts of polyethylene glycol methacrylate phosphate are added, heated to 65°C and stirred for 40 minutes, and then 3 parts of potassium persulfate are added and stirred for 1 hour, and finally the temperature is reduced and cooled to obtain the fluorophosphorus monomer modified water-based acrylic emulsion.

[0061] The preparation method of the capsaicin is as follows: by weight, 60 parts of dried devil peppers are deseeded and destalked, added to 100 parts of anhydrous ethanol, crushed with a tissue crusher, and then placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 95W, the time is 40 minutes, and then the ultrasonic solution is filtered to obtain a first filtrate and a first filter residue, the first filter residue is subjected to a second ultrasonic filtration treatment using the same process and parameters to obtain a second filtrate and a second filter residue, the first filtrate and the second filtrate are mixed and evaporated at 50° C. for 3 hours to obtain a capsaicin concentrate, and then it is completely dried at 60° C. to obtain capsaicin.

[0062] The Scoville heat scale of the above-mentioned capsaicin is 50,000.

[0063] The preparation method of the porous boron nitride hollow microspheres is as follows: 17 parts of boric acid and 24 parts of urea are dissolved in 100 parts of deionized water, stirred at 45°C for 16 hours, and then the boron nitride precursor microspheres are obtained by spray drying. The parameters of the spray drying method are: the inlet flow rate is 6 ml / min, the nozzle pressure is 2 bar, and the inlet temperature is 105°C. Then the boron nitride precursor microspheres are placed in a high-temperature tubular furnace and calcined in a nitrogen atmosphere. The calcination parameters are: heating from room temperature to 460°C at 5°C / min and keeping the temperature for 2 hours, then continuing to heat to 1000°C at 5°C / min and keeping the temperature for 2 hours, and then naturally cooling to room temperature to obtain a white product. The white product was completely submerged with a 1 mol / L hydrochloric acid solution, stirred at room temperature for 7 h, and then filtered to obtain a filtered product. The filtered product was then washed three times with a mixed washing solution of deionized water and anhydrous ethanol in a mass ratio of 1:1. Each washing required that the filtered product be completely submerged with the washing solution. Finally, the washed product was dried to obtain porous boron nitride hollow microspheres.

[0064] The preparation method of the above epoxy resin is as follows: by weight, 28 parts of furfurylamine, 12 parts of bisphenol A diglycidyl ether and 11 parts of dimethylformamide are uniformly mixed and reacted at 58° C. for 4 hours to obtain the epoxy resin.

[0065] The present invention also provides a method for preparing an anticorrosive coating for a ship bottom, comprising the following steps:

[0066] S1: Dispersion of filler: Deionized water, boron nitride coated capsaicin filler, boron nitride modified fluorosilicone copolymer and dispersant were added into a stirring tank according to the proportion, and the filler dispersion solution was obtained by high-speed dispersion at 900 rpm for 35 minutes.

[0067] S2: Prepare coating: inject the filler dispersion solution obtained in S1 into the paint mixing tank, and continue to add fluorophosphorus monomer modified water-based acrylic emulsion, epoxy resin, preservative, film former and defoamer into the paint mixing tank, stir at 140 rpm for 35 minutes at 78°C, and cool to room temperature after stirring.

[0068] Example 3

[0069] An anticorrosive coating for the bottom of a ship is prepared from the following components in parts by weight: 14 parts of a boron nitride-coated capsaicin filler, 16 parts of a boron nitride-modified fluorosilicon copolymer, 40 parts of a fluorophosphorus monomer-modified waterborne acrylic emulsion, 8 parts of an epoxy resin, 16 parts of an ethylene glycol butyl ether film former, 3 parts of a polyether-modified silicone oil defoamer, 4 parts of polyacrylic acid sodium salt, 5 parts of 4,5-dichloro-N-octyl-4-isothiazoline-3-one and 8 parts of deionized water.

[0070] The preparation method of the boron nitride coated capsaicin filler is as follows: after mixing 70 parts of porous boron nitride hollow microspheres, 18 parts of capsaicin and 80 parts of ethanol in parts by weight, the mixture is placed in an ultrasonic cleaner for ultrasonic treatment. The setting parameters of the ultrasonic cleaner are: 90W, the time is 25 minutes, and the mixture is filtered after ultrasonic treatment. The filtered product is washed once with a mixed solution of ethanol and water in a mass ratio of 1:1 to remove excess capsaicin on the surface of the porous boron nitride hollow microspheres, and then dried to obtain the boron nitride coated capsaicin filler.

[0071] The average particle size of the boron nitride coated capsaicin filler is 1500 nm.

[0072] The preparation method of the boron nitride modified fluorosilicon copolymer is as follows: in a nitrogen atmosphere, 28 parts of dodecafluoroheptyl methacrylate, 14 parts of methacryloyloxypropyl trimethoxysilane, 56 parts of glycidyl methacrylate, 56 parts of butyl acrylate and 3 parts of azobisisobutyronitrile are mixed evenly to obtain a fluorosilicon prepolymer solution for use. 26 parts of methyl methacrylate and 5 parts of boron nitride are mixed evenly and heated to 80°C, and then the fluorosilicon prepolymer solution is dripped therein, and the reaction is stirred for 3 hours after the dripping is completed. After the reaction is completed, the temperature is cooled to room temperature to obtain a boron nitride modified fluorosilicon copolymer.

[0073] The preparation method of the fluorophosphorus monomer modified water-based acrylic emulsion is as follows: in parts by weight, 14 parts of methyl methacrylate, 26 parts of butyl acrylate, 5 parts of acrylic acid, 3 parts of isooctyl acrylate, 5 parts of glycidyl methacrylate, 3 parts of sodium lauryl sulfate and 40 parts of deionized water are mixed and stirred for 50 minutes for pre-emulsification treatment, and then 13 parts of octafluoropentyl methacrylate and 12 parts of polyethylene glycol methacrylate phosphate are added, heated to 70°C and stirred for 50 minutes, and then 4 parts of potassium persulfate are added and stirred for 1 hour, and finally the temperature is reduced and cooled to obtain the fluorophosphorus monomer modified water-based acrylic emulsion.

[0074] The preparation method of the capsaicin is as follows: by weight, 60 parts of dried devil peppers are deseeded and destalked, added to 100 parts of anhydrous ethanol, crushed with a tissue crusher, and then placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 100W, time is 50min, and then the ultrasonic solution is filtered to obtain a first filtrate and a first filter residue, the first filter residue is subjected to a second ultrasonic filtration treatment using the same process and parameters to obtain a second filtrate and a second filter residue, the first filtrate and the second filtrate are mixed and evaporated at 50°C for 3h to obtain a capsaicin concentrate, and then dried completely at 70°C to obtain capsaicin.

[0075] The Scoville heat scale of the above-mentioned capsaicin is 70,000.

[0076] The preparation method of the porous hollow boron nitride microspheres is as follows: 27 parts of boric acid and 54 parts of urea are dissolved in 100 parts of deionized water, stirred at 45°C for 20 hours, and then the boron nitride precursor microspheres are obtained by spray drying. The parameters of the spray drying method are: the inlet flow rate is 8 ml / min, the nozzle pressure is 2 bar, and the inlet temperature is 105°C. Then the boron nitride precursor microspheres are placed in a high-temperature tube furnace and calcined in a nitrogen atmosphere. The calcination parameters are: heating from room temperature to 480°C at 5°C / min and keeping the temperature for 2 hours, then continuing to heat to 1100°C at 5°C / min and keeping the temperature for 2 hours, and then naturally cooling to room temperature to obtain a white product. The white product was completely submerged with a 1 mol / L hydrochloric acid solution, stirred at room temperature for 8 h, and then filtered to obtain a filtered product. The filtered product was then washed three times with a mixed washing solution of deionized water and anhydrous ethanol in a mass ratio of 1:1. Each washing required that the filtered product be completely submerged with the washing solution. Finally, the washed product was dried to obtain porous boron nitride hollow microspheres.

[0077] The preparation method of the above epoxy resin is as follows: by weight, 32 parts of furfurylamine, 16 parts of bisphenol A diglycidyl ether and 14 parts of dimethylformamide are uniformly mixed and reacted at 62° C. for 4 hours to obtain the epoxy resin.

[0078] The present invention also provides a method for preparing an anticorrosive coating for a ship bottom, comprising the following steps:

[0079] S1: Dispersion of filler: Deionized water, boron nitride coated capsaicin filler, boron nitride modified fluorosilicone copolymer and dispersant were added into a stirring tank according to the proportion, and the filler dispersion solution was obtained by high-speed dispersion at 1100 rpm for 40 minutes.

[0080] S2: Prepare coating: inject the filler dispersion solution obtained in S1 into the paint mixing tank, and continue to add fluorophosphorus monomer modified water-based acrylic emulsion, epoxy resin, preservative, ethylene glycol butyl ether film-forming agent, and defoaming agent into the paint mixing tank, stir at 180 rpm for 45 minutes at 80°C, and cool to room temperature after stirring.

[0081] Example 4

[0082] An anticorrosive coating for the bottom of a ship is prepared from the following components in parts by weight: 16 parts of boron nitride-coated capsaicin filler, 18 parts of boron nitride-modified fluorosilicone copolymer, 45 parts of fluorophosphorus monomer-modified water-based acrylic emulsion, 10 parts of epoxy resin, 18 parts of film-forming agent, 4 parts of polyether-modified silicone oil defoamer, 5 parts of ammonium polyacrylate, 6 parts of 4,5-dichloro-N-octyl-4-isothiazoline-3-one and 10 parts of deionized water.

[0083] The preparation method of the above-mentioned boron nitride coated capsaicin filler is as follows: 80 parts of porous boron nitride hollow microspheres, 20 parts of capsaicin, and 80 parts of ethanol are mixed evenly by weight, and then placed in an ultrasonic cleaner for ultrasonic treatment. The setting parameters of the ultrasonic cleaner are: 100W, time is 30min, and after ultrasonic treatment, it is filtered, and the filtered product is washed once with a mixed solution of ethanol and water in a mass ratio of 1:1 to remove excess capsaicin on the surface of the porous boron nitride hollow microspheres, and then dried to obtain the boron nitride coated capsaicin filler.

[0084] The average particle size of the boron nitride coated capsaicin filler is 2000 nm.

[0085] The preparation method of the boron nitride modified fluorosilicon copolymer is as follows: in a nitrogen atmosphere, 30 parts of dodecafluoroheptyl methacrylate, 15 parts of methacryloyloxypropyl trimethoxysilane, 60 parts of glycidyl methacrylate, 60 parts of butyl acrylate and 4 parts of azobisisobutyronitrile are mixed evenly to obtain a fluorosilicon prepolymer solution for use. 30 parts of methyl methacrylate and 6 parts of boron nitride are mixed evenly and heated to 85°C, and then the fluorosilicon prepolymer solution is dripped therein, and after the dripping is completed, the reaction is stirred for 4 hours, and after the reaction is completed, the temperature is cooled to room temperature to obtain a boron nitride modified fluorosilicon copolymer.

[0086] The preparation method of the fluorophosphorus monomer modified water-based acrylic emulsion is as follows: in parts by weight, 15 parts of methyl methacrylate, 28 parts of butyl acrylate, 6 parts of acrylic acid, 4 parts of isooctyl acrylate, 6 parts of glycidyl methacrylate, 4 parts of sodium lauryl sulfate and 45 parts of deionized water are mixed and stirred for 60 minutes for pre-emulsification treatment, and then 15 parts of 2,2,2-trifluoroethyl methacrylate and 15 parts of polyethylene glycol methacrylate phosphate are added, heated to 80°C and stirred for 60 minutes, and then 5 parts of potassium persulfate are added and stirred for 1 hour, and finally the temperature is reduced and cooled to obtain the fluorophosphorus monomer modified water-based acrylic emulsion.

[0087] The preparation method of the capsaicin is as follows: by weight, 70 parts of dried devil peppers are deseeded and stalked, added to 100 parts of anhydrous ethanol, crushed with a tissue crusher, and then placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 110W, the time is 60 minutes, and then the ultrasonic solution is filtered to obtain a first filtrate and a first filter residue, the first filter residue is subjected to a second ultrasonic filtration treatment using the same process and parameters to obtain a second filtrate and a second filter residue, the first filtrate and the second filtrate are mixed and evaporated at 55° C. for 4 hours to obtain a capsaicin concentrate, and then it is completely dried at 80° C. to obtain capsaicin.

[0088] The Scoville heat scale of the above-mentioned capsaicin is 80,000.

[0089] The preparation method of the porous hollow boron nitride microspheres is as follows: 30 parts of boric acid and 60 parts of urea are dissolved in 100 parts of deionized water, stirred at 50°C for 24 hours, and then the boron nitride precursor microspheres are obtained by spray drying. The parameters of the spray drying method are: the inlet flow rate is 10 ml / min, the nozzle pressure is 3 bar, and the inlet temperature is 120°C. Then the boron nitride precursor microspheres are placed in a high-temperature tubular furnace and calcined in a nitrogen atmosphere. The calcination parameters are: heating from room temperature to 500°C at 5°C / min and keeping the temperature for 2 hours, then continuing to heat to 1200°C at 5°C / min and keeping the temperature for 2 hours, and then naturally cooling to room temperature to obtain a white product. The white product was completely submerged with a 1 mol / L hydrochloric acid solution, stirred at room temperature for 10 h, and then filtered to obtain a filtered product. The filtered product was then washed three times with a mixed washing solution of deionized water and anhydrous ethanol in a mass ratio of 1:1. Each washing required that the filtered product be completely submerged with the washing solution. Finally, the washed product was dried to obtain porous boron nitride hollow microspheres.

[0090] The preparation method of the above epoxy resin is as follows: by weight, 35 parts of furfurylamine, 18 parts of bisphenol A diglycidyl ether and 15 parts of dimethylformamide are uniformly mixed and reacted at 65° C. for 5 hours to obtain the epoxy resin.

[0091] The present invention also provides a method for preparing an anticorrosive coating for a ship bottom, comprising the following steps:

[0092] S1: Dispersion of filler: Deionized water, boron nitride coated capsaicin filler, boron nitride modified fluorosilicone copolymer and dispersant were added into a stirring tank according to the proportion, and the filler dispersion solution was obtained by high-speed dispersion at 1200 rpm for 50 min.

[0093] S2: Prepare coating: inject the filler dispersion solution obtained in S1 into the paint mixing tank, and continue to add fluorophosphorus monomer modified water-based acrylic emulsion, epoxy resin, preservative, film-forming agent, and defoaming agent into the paint mixing tank, stir at 200 rpm at 85°C for 50 minutes, and cool to room temperature after stirring.

[0094] Example 5

[0095] The method is basically the same as Example 1, except that the calcination temperature for preparing the porous hollow boron nitride microspheres is 1200° C., so the average particle size of the obtained boron nitride coated capsaicin filler is 2000 nm.

[0096] Comparative Example 1

[0097] The method is basically the same as Example 1, except that the porous boron nitride hollow microspheres in the coating are not coated with capsaicin.

[0098] Comparative Example 2

[0099] It is basically the same as Example 1, except that the prepared coating porous boron nitride hollow microspheres and capsaicin are added separately, so there is no coating relationship between the two.

[0100] Comparative Example 3

[0101] The method is basically the same as Example 1, except that no fluorine-containing monomer is added in the preparation of the fluorophosphorus monomer-modified aqueous acrylic emulsion.

[0102] Comparative Example 4

[0103] The method is basically the same as Example 1, except that no phosphorus-containing monomer is added in the preparation of the fluorophosphorus monomer-modified aqueous acrylic emulsion.

[0104] Comparative Example 5

[0105] The method is basically the same as Example 1, except that dodecafluoroheptyl methacrylate is not added in the preparation of the boron nitride modified fluorosilicone copolymer, so the fluorosilicone copolymer cannot be formed.

[0106] Characterization Test

[0107] In order to comprehensively characterize the samples, a variety of characterization methods were used and the corresponding experimental parameters were set. The acceleration voltage of the scanning electron microscope (SEM) was set in the range of 10-20 kV, the probe current was between 10-100 μA, and the working distance was between 5-15 mm. In the X-ray diffraction (XRD) experiment, the incident angle range was set to 5°-80°, the scanning speed was 0.02° / min, and the Cu Kα ray wavelength was 1.54 Å. In the Fourier transform infrared spectroscopy (FTIR) experiment, an infrared light source was used, and the spectral range was set to 500-4000 cm -1 , with a resolution of 4 cm -1 .

[0108] Figure 1 This is a scanning electron microscope morphology of the porous hollow boron nitride microspheres prepared in Example 1 of the present invention. It can be observed from the figure that the surface of the microspheres presents a porous structure, and this porous property is conducive to the long-term release of capsaicin and improves the life of the coating.

[0109] Figure 2 This is a scanning electron microscope image of the boron nitride coated capsaicin filler prepared in Example 1 of the present invention. It can be seen that the boron nitride particles are uniformly coated on the surface of the capsaicin filler, and this coating structure helps to protect the filler and provide better stability.

[0110] Figure 3 This is a phase analysis diagram of the porous boron nitride hollow microspheres prepared in Example 1 of the present invention. The crystal structure of the porous boron nitride in the sample was confirmed by X-ray diffraction analysis, and its diffraction peaks were consistent with those of standard boron nitride.

[0111] Figure 4 This is a phase analysis diagram of the boron nitride coated capsaicin filler prepared in Example 1 of the present invention. The X-ray diffraction analysis results show the crystal structure of the boron nitride and capsaicin in the sample, and correspond to the diffraction peaks of standard boron nitride and capsaicin.

[0112] Figure 5 The Fourier transform infrared spectrum of the boron nitride modified fluorosilicon copolymer of Example 1 of the present invention is shown in Figure 1. Due to the copolymerization of glycidyl methacrylate, the characteristic peak of -CH(O)CH- of symmetrical stretching vibration is observed at 907 cm−1. −1 The absorption at -CH 2 - is caused by bending vibration. Located at 1727 cm −1 and 1145 cm −1 The peaks are attributed to the C=O stretching vibration and CO stretching vibration of the ester. −1 The peak at 688 cm is the characteristic absorption of the stretching vibration of the CF bond, while the peak at 688 cm −1The absorption at -CF 2 -group rocking vibration. In this study, 1082 cm −1 The peaks at 1375 and 785 cm are usually attributed to the stretching vibration of Si-O-Si bonds. −1 All come from the vibration of BN.

[0113] In summary, the present invention comprehensively characterized the sample prepared in Example 1 by scanning electron microscopy morphology observation, phase analysis, FTIR and other characterization methods. The results show that the prepared porous boron nitride hollow microspheres have a porous structure, and the boron nitride coated capsaicin filler forms a uniform coating layer. The phase analysis and FTIR results further prove the boron nitride crystal structure in the sample and the chemical structure of the boron nitride modified fluorine silicon copolymer. These characterization results provide strong evidence for the practical application of the present invention and provide a basis for further research and optimization.

[0114] Performance Testing

[0115] Hardness: Hardness is one of the important indicators in coating applications. The hardness of coatings is determined in accordance with the standard GB / T 6739-2006 "Determination of film hardness of paints and varnishes by pencil method".

[0116] Wear resistance: Wear resistance is also one of the important indicators in coating applications. The wear resistance of coatings refers to the determination of wear resistance of paints and varnishes in GB / T1768-2006. The coating is first evenly coated on a solid flat surface. Subsequently, the prepared sample is fixed on the rotating disk of the Taber wear tester. During the test, a rotor with a standard wear head wears the coating within a set 1000 rotation cycle while applying a constant weight of 1000g. By accurately measuring the mass loss of the coating after these 1000 rotations (in milligrams), the wear resistance data of the coating can be obtained. These data not only provide an in-depth understanding of the wear resistance of the coating, but also provide a scientific basis for the selection and use of the coating in practical applications.

[0117] Solvent resistance requires testing of seawater resistance, acid resistance, oil resistance, and alkali resistance. The seawater resistance test refers to GB / T9274-1988 standard, the test environment is seawater, and the test time is 300 days; the acid resistance refers to GB / T9274-1988 standard, the test environment is 50% H 2 SO 4, the test time is 168h; the oil resistance test is carried out according to GB / T9274-1988 standard, the test environment is diesel, and the test time is 168h; the alkali resistance test is carried out according to GB / T9274-1988 standard, the test environment is 30% NaOH, and the test time is 168h. After the solvent resistance test, the coating is considered qualified if it does not bubble, crack, fall off, or change color, otherwise it is considered unqualified.

[0118] The aging resistance test is carried out in accordance with GB / T9276-19966 standard; the adhesion test is carried out in accordance with GB / T5210-2006 standard.

[0119] Test for inhibiting the attachment of marine organisms: The steel plates coated with anti-corrosion paint are placed in seawater suitable for the growth of marine organisms for testing for 3 months. After the test, check whether there is any marine organism attachment.

[0120] The properties of the coatings of Examples 1 to 5 and Comparative Examples 1 to 5 are summarized in Table 2.

[0121] The main difference between Comparative Example 1 and Example 1 is whether the medium-porous boron nitride hollow microspheres in the coating are coated with capsaicin. It can be seen from Table 2 that the filler coated with capsaicin can significantly inhibit the attachment of marine organisms. This is because capsaicin extracted from devil pepper can inhibit the attachment of marine organisms.

[0122] The main difference between Comparative Example 2 and Example 1 is whether there is a coating relationship between the porous boron nitride hollow microspheres and capsaicin. From Table 2, it can be seen that if capsaicin is not coated by the boron nitride hollow microspheres, the hardness, wear resistance and oil resistance of the coating will decrease.

[0123] The main difference between Comparative Example 3 and Example 1 is whether a fluorine-containing monomer is added in the preparation of the fluorine-phosphorus monomer-modified water-based acrylic emulsion. It can be seen from Table 2 that the fluorine-containing monomer can improve the salt resistance, acid and alkali resistance and oil resistance of the coating.

[0124] The main difference between Comparative Example 4 and Example 1 is whether a phosphorus-containing monomer is added in the preparation of the fluorophosphorus monomer-modified waterborne acrylic emulsion. From Table 2, it can be seen that the addition of a phosphorus-containing monomer can improve the adhesion and salt resistance, acid and alkali resistance, and oil resistance of the coating.

[0125] The main difference between Comparative Example 5 and Example 1 is whether dodecafluoroheptyl methacrylate is added in the preparation of boron nitride modified fluorosilicone copolymer and whether a fluorosilicone copolymer can be formed. From Table 2, it can be seen that the fluorosilicone copolymer can improve the salt resistance, acid and alkali resistance and oil resistance of the coating.

[0126] In summary, the design of capsaicin coated with boron nitride in the present invention shows multiple advantages in the anti-corrosion coating for ship bottom, including enhancing the wear resistance of the coating, extending the service life, repelling marine organisms, reducing the risk of biocorrosion, forming a durable and stable protective layer, providing excellent anti-corrosion function, achieving a perfect combination of hydrophobicity, anti-fouling and anti-corrosion, having self-repairing ability, and improving water resistance, corrosion resistance and substrate adhesion through modified waterborne acrylic emulsion. In addition, the key reagents in the anti-corrosion coating for ship bottom work together to provide strong and comprehensive anti-corrosion protection to ensure the safe and stable operation of the ship. These innovative designs provide important technical support for the application of coating materials in multiple fields.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. An anti-corrosion coating for the bottom of a ship, characterized in that: The invention is prepared from the following components in parts by weight: 8-16 parts of boron nitride coated capsaicin filler, 10-18 parts of boron nitride modified fluorine silicon copolymer, 30-45 parts of fluorine phosphorus monomer modified waterborne acrylic emulsion, 6-10 parts of epoxy resin, 10-18 parts of film former, 2-4 parts of defoamer, 2-5 parts of dispersant, 3-6 parts of initiator, 3-6 parts of preservative and 5-10 parts of deionized water; The preparation method of the boron nitride coated capsaicin filler is as follows: after mixing 50 to 80 parts of porous boron nitride hollow microspheres, 10 to 20 parts of capsaicin, and 80 parts of ethanol by weight, the mixture is placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 80 to 100W, the time is 15 to 30 minutes, and after ultrasonic treatment, the mixture is filtered, and the filtered product is washed once with a mixed solution of ethanol and water in a mass ratio of 1:1 to remove excess capsaicin on the surface of the porous boron nitride hollow microspheres, and the boron nitride coated capsaicin filler is obtained after drying; The average particle size of the boron nitride coated capsaicin filler is 500-2000 nm; The preparation method of the boron nitride modified fluorosilicone copolymer is as follows: in a nitrogen atmosphere, 22 to 30 parts by weight of dodecafluoroheptyl methacrylate, 11 to 15 parts of methacryloyloxypropyl trimethoxysilane, 44 to 60 parts of glycidyl methacrylate, 44 to 60 parts of butyl acrylate and 2 to 4 parts of azobisisobutyronitrile are mixed evenly to obtain a fluorosilicone prepolymer liquid for standby use; 15 to 30 parts of methyl methacrylate and 3 to 6 parts of boron nitride are mixed evenly and heated to 65 to 85° C., the fluorosilicone prepolymer liquid is dripped into the prepolymer liquid drop by drop, and after the dripping is completed, the reaction is stirred for 2 to 4 hours, and after the reaction is completed, the temperature is cooled to room temperature to obtain the boron nitride modified fluorosilicone copolymer; The preparation method of the fluorophosphorus monomer modified water-based acrylic emulsion is as follows: by weight, 10 to 15 parts of methyl methacrylate, 20 to 28 parts of butyl acrylate, 3 to 6 parts of acrylic acid, 2 to 4 parts of isooctyl acrylate, 3 to 6 parts of glycidyl methacrylate, 2 to 4 parts of sodium dodecyl sulfate and 25 to 45 parts of deionized water are mixed and stirred for 30 to 60 minutes for pre-emulsification treatment, 8 to 15 parts of fluorine-containing monomers and 8 to 15 parts of phosphorus-containing monomers are added, heated to 60 to 80° C. and stirred for 30 to 60 minutes, 2 to 5 parts of potassium persulfate are added, stirred for 1 hour, and finally cooled to obtain the fluorophosphorus monomer modified water-based acrylic emulsion, wherein the capsaicin The preparation method is as follows: by weight, 50-70 parts of dried devil peppers are deseeded and destalked, added to 100 parts of anhydrous ethanol, crushed with a tissue crusher, placed in an ultrasonic cleaner for ultrasonic treatment, the ultrasonic cleaner setting parameters are: 90-110W, the time is 30-60min, the ultrasonic solution is filtered to obtain a first filtrate and a first filter residue, the first filter residue is subjected to a second ultrasonic filtration treatment using the same process and parameters to obtain a second filtrate and a second filter residue, the first filtrate and the second filtrate are mixed and evaporated at 45-55°C for 2-4h to obtain capsaicin concentrate, and the concentrate is completely dried at 50-80°C to obtain capsaicin; The preparation method of the porous boron nitride hollow microspheres is as follows: 15-30 parts of boric acid and 30-60 parts of urea are dissolved in 100 parts of deionized water, stirred at 40-50° C. for 12-24 hours, a spray drying method is used to obtain boron nitride precursor microspheres, the boron nitride precursor microspheres are placed in a high-temperature tube furnace, and calcined in a nitrogen atmosphere, wherein the calcination parameters are as follows: heating from room temperature to 450-500° C. at 5° C. / min and keeping the temperature for 2 hours, and then heating to 950-1200° C. at 5° C. / min and keeping the temperature for 2 hours, and naturally cooling to room temperature to obtain a white product, and completely submerging the white product with a 1 mol / L hydrochloric acid solution, stirring at room temperature for 6-10 hours, and then filtering to obtain a filtered product, and washing the filtered product three times with a mixed washing liquid of deionized water and anhydrous ethanol with a mass ratio of 1:1, and each washing needs to completely submerge the filtered product with the washing liquid, and finally drying the washed product to obtain the porous boron nitride hollow microspheres; The mass ratio of the boric acid to urea is 1:

2.

2. The anticorrosive coating for the bottom of a ship as claimed in claim 1, characterized in that: The Scoville heat of the capsaicin is 40,000 to 80,000.

3. The anticorrosive coating for the bottom of a ship as claimed in claim 2, characterized in that: The parameters of the spray drying method are: inlet flow rate is 5-10 ml / min, nozzle pressure is 1-3 bar, and inlet temperature is 100-120°C.

4. The anticorrosive coating for the bottom of a ship as claimed in claim 1, characterized in that: The mass ratio of dodecafluoroheptyl methacrylate, methacryloyloxypropyltrimethoxysilane, glycidyl methacrylate and butyl acrylate is 2:1:4:

4.

5. The anticorrosive coating for the bottom of a ship as claimed in claim 1, characterized in that: The fluorine-containing monomer is 2,2,2-trifluoroethyl acrylate or 2,2,2-trifluoroethyl methacrylate or octafluoropentyl methacrylate; The phosphorus-containing monomer is polyethylene glycol methacrylate phosphate.

6. The anticorrosive coating for the bottom of a ship as claimed in claim 1, characterized in that: The preparation method of the epoxy resin is as follows: by weight, 25-35 parts of furfurylamine, 10-18 parts of bisphenol A diglycidyl ether and 10-15 parts of dimethylformamide are uniformly mixed and reacted at 55-65° C. for 3-5 hours to obtain the epoxy resin, wherein the preservative is 4,5-dichloro-N-octyl-4-isothiazoline-3-one; The film former is ethylene glycol butyl ether or ethylene glycol ether; The defoamer is an organosilicon defoamer or a polyether modified silicone oil defoamer; The dispersant is polyacrylic acid sodium salt or polyacrylic acid ammonium salt; The initiator is ammonium persulfate.

7. A method for preparing an anticorrosive coating for a ship bottom as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Dispersion of filler: Deionized water, boron nitride coated capsaicin filler, boron nitride modified fluorosilicone copolymer and dispersant are added into a stirring tank according to the proportion, and dispersed at 800-1200 rpm for 30-50 min to obtain a filler dispersion solution. S2: Prepare coating: inject the filler dispersion solution obtained in S1 into the paint mixing tank, continue to add fluorophosphorus monomer modified water-based acrylic emulsion, epoxy resin, preservative, film-forming agent, defoaming agent into the paint mixing tank, stir at 100-200 rpm for 30-50 minutes at 75-85°C, and cool to room temperature after stirring.

Citation Information

Patent Citations

  • Flexile epoxy anticorrosion paint

    CN101260273B

  • Marine antifouling paint

    CN108948837A

  • Modified fluorosilicone acrylate resin, antifouling and antibacterial coating and preparation method thereof

    CN113999333A

Cited By

  • High performance anticorrosive coating for ship bottom and its preparation method

    CN122628621A